Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1987
DOI: 10.1007/bf00391442
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of tumor volume in localized Ewing's sarcoma of bone in children and adolescents

Abstract: A total of 60 consecutive patients with localized Ewing's sarcoma of bone who were entered into the Cooperative Ewing's Sarcoma Study of the German Society of Pediatric Oncology from January 1981 until April 1985 were evaluable for tumor volume at diagnosis. The tumor volume was calculated from plain X-rays and CT scans as ellipsoidal or cylindrical depending on the tumor configuration and presence or absence of a soft tissue component. The 3-year disease-free survival rate according to Kaplan-Meier life table… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
3
7

Year Published

1991
1991
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(95 citation statements)
references
References 7 publications
1
84
3
7
Order By: Relevance
“…In contrast with the results observed for other locations [4,6,7,9,[12][13][14][15][16]19], the outcome for our series was unrelated to tumor volume, type of local treatment, histology (ES vs. PNET), LDH serum levels, and neoadjuvant chemotherapy protocols.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast with the results observed for other locations [4,6,7,9,[12][13][14][15][16]19], the outcome for our series was unrelated to tumor volume, type of local treatment, histology (ES vs. PNET), LDH serum levels, and neoadjuvant chemotherapy protocols.…”
Section: Discussioncontrasting
confidence: 99%
“…An EFS of 70% was achieved for patients with localized disease, and OS reached 80%. [4][5][6][7][8][17][18][19][20][21] The outcome of metastatic patients remains dismal, especially for patients with bone and BM involvement. [4][5][6][9][10][11] Rodriguez Galindo et al 23 suggested risk stratification, taking into account simple clinical features, such as age, stage, tumor volume, localization and histological response to chemotherapy, to modulate treatment intensification in different subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] In the past decade, ESFT outcome was improved largely through a multidisciplinary strategy based on surgery, radiotherapy and intensified chemotherapy regimens, [4][5][6] whereas large studies have identified risk factors associated with the worse prognosis. [4][5][6][7][8] Since the late 1980s, high-dose chemotherapy (HDC), followed by stem-cell rescue, has been proposed to improve the outcome of patients with poor-prognosis ESFT. Although many studies have been published, the role of HDC in ESFT remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…At MRI, tumor diameters were measured in 3 planes: transverse, sagittal and coronal. The tumor volume was calculated according to Göbel et al (1987) and then plotted as a function of time (Figures 1 and 2).…”
Section: Methodsmentioning
confidence: 99%